Gap Analysis of Customer Expectation and Perception of Professionalism among Nigeria Police Officers: The SERVICOM Perspective - Olowe; Sunday and Ogunode, Temitope; Olatunde, Philips (British Journal of Marketing Studies, 2020)
This paper investigated gap analysis of customer expectation and perception of professionalism among Nigeria police officers: the SERVICOM perspective. The study specifically examined the effect of SERVICOM on professionalism of service as well as gap between customer expectation and perception of Nigeria police service. Descriptive survey design was adopted through which structured questionnaire was used to collect data from the field. The population of the study comprised of all police officers from all ranks and files within Ekiti and Ondo States as well as consumers of police services. Convenience sampling technique was used to select 4,000 respondents which included 2,000 police officers from different ranks and files as well as 2,000 consumers of police services within the two states. Descriptive statistics was used to analyze the research questions while t-test and Chi-square (?2) were used to test hypothesis one and two respectively. The level of significance was set at 5%. Findings revealed that there was significant difference between customers’ expectation and perception regarding the quality of service provided by the Nigeria Police Force. It was therefore recommended among others that Regulatory authorities in the Nigerian Police Force should take steps to ensure that the operations of the Force are, to some extent, consistent with the expectations of customers as this will help to minimize the discrepancies between customers’ expectation of services and the actual service realized from the Force.